The Effectiveness of the Problem Based Learning Module on Student Learning Outcomes in the Material of One Variable Linear Equations and Inequalities at SMP Negeri 29 Sijunjung - Elsa Putri; Rahmi Rahmi; Mulia Suryani (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This research is motivated by the low results of students' mathematics learning. The purpose of this study was to find out whether the use of problem-based learning (PBL)-based modules was effective in increasing student learning outcomes in the material of one-variable linear equations and inequalities at SMP Negeri 29 Sijunjung. This type of research is experimental research using a quantitative approach with the one-group pretest-posttest design. The research population was all students of class VII SMP Negeri 29 Sijunjung. The sampling technique used in this study is random sampling. The sample class for this study was class VII 3. The research instrument used was the pretest and posttest, in the form of an essay test with a reliability of 0.696. Furthermore, testing the hypothesis using the t test. The results showed that after using PBL-based modules it had an average value of 71.96 and before implementing PBL-based modules it had an average value of 16.05. The results of the hypothesis test obtained tcount = 4.89 and ttable = 1.708, then tcount ttable so that the hypothesis is accepted. Thus it can be concluded that the Problem Based Learning (PBL) based module is effective in improving students' mathematics learning outcomes.